Touching for knowing : cognitive psychology of haptic manual perception - Hatwell, Yvette; Streri, Arlette; Gentaz, Edouard (Advances in consciousness research, 2003)
The dominance of vision is so strong in sighted people that touch is sometimes considered as a minor perceptual modality. However, touch is a powerful tool which contributes significantly to our knowledge of space and objects. Its intensive use by blind persons allows them to reach the same levels of knowledge and cognition as their sighted peers. In this book, specialized researchers present the recent state of knowledge about the cognitive functioning of touch. After an analysis of the neurophysiology and neuropsychology of touch, exploratory manual behaviors, intramodal haptic (tactual-kines.